The Influence of Flipbook Electronic Module and Students' Interest in Reading on Digital Literature Ability of State High School Students in Pandeglang Regency - Bayu Purnama Galuh; Eman Supriatna; Agung Nurul Hidayat (Peneliti.net, 2022)
The times are changing so fast, it is hoped that educational practitioners must continue to develop their knowledge. Technology has become a very important instrument in digital electronics and information technology and affects the world of education such as digital-based teaching materials in the form of electronic modules. The electronic module is one of the independent teaching materials that is systematically arranged in learning activities to achieve learning objectives which are presented in electronic form. This study aims to determine the effect of the application of the electronic module flipbook and reading interest on students' digital literacy skills. The sample in this study is class X.1 and X.7 which represents the total population at SMAN 7 Pandeglang. sampling technique using Cluster Random Sampling. Based on the significance value, the flipbook module has an effect on students' digital literacy skills. In addition, reading interest has an effect on students' digital literacy skills and the flipbook module and reading interest simultaneously have a significant effect on digital literacy skills for state high school students in Pandeglang Regency